Design for hydraulic pressure system of mobile inspection flat equipment of tractor - TAN Li-hong; YIN Xia-fang; HE Yong (浙江大学学报. 农业与生命科学版)
The design of hydraulic pressure system and flat structure were introduced. In order to overcome the defects existing in the original hydraulic pressure flat system, such as unsteadiness and vibration during elevating and descending of flat, the hydraulic pressure synchronous loop was designed. At the same time, if hydraulic pressure components were chosen properly, the equality of flux and the stability of velocity can be ensured. The results of practical application proved that the hydraulic system was suitable for tractor performance inspection.